A SOCIOLOGY LEARNING MODEL FOR STRENGHTHENING THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN SENIOR HIGH SCHOOLS - Ismail, Mail; Wilodati, Wilodati; Nurbayani, Siti (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
This study aims to develop a hypothetical learning model to strengthen the implementation of deep learning approaches in senior high schools (SMA). The research employs a qualitative methodology utilizing a 4D development model (Define, Design, Develop, Disseminate). In the Define stage, a needs analysis was conducted to identify problems and instructional requirements in sociology education. This was achieved through in-depth interviews with sociology teachers, driving teachers, school principals, and an extensive literature review. The findings informed the foundational concepts and specific needs for a deep learning- focused instructional framework. The Design stage involved developing the ISMAIL learning Model, which stands for Inovatif (Innovative), Sistematis (Systematic), Mandiri (Independent), Aktif (Active), Interaktif (Interactive), and Lestari (Sustainable). The design was guided by educational theories emphasizing critical thinking, active engagement, and sustainable learning practices. In the Develop stage, the model underwent iterative testing in controlled educational settings to refine its application and effectiveness. Feedback from educators and students was used to optimize the model for fostering deeper cognitive engagement and comprehensive skill development. Finally, the Disseminate stage focused on sharing the refined ISMAIL learning Model through academic publications, workshops, and seminars to promote its adoption and adaptability in diverse educational contexts.This methodological framework demonstrates the model’s capacity to support the integration of deep learning principles in sociology education, aiming to enhance students’ understanding, foster active participation, and develop critical social competencies. Future research is necessary to validate the model’s effectiveness and explore its potential across varied educational settings.